Different kinds of reactive oxygen and nitrogen species were detected in colon and breast tumors - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 2001)
Several studies have shown the involvement of reactive oxygen species (ROS; O-2 .-, hypochlorite, hydroxyl radical, hydrogen peroxide) in carcinogenesis. With certain pathologies, nitric oxide (NO) is formed and can interact with superoxide radical (O-2 .-) resulting in the propagation of the highly reactive species, peroxynitrite. In order to study the molecular mechanisms underlying the ability of reactive oxygen and nitrogen species (RONS) to mediate carcinogenesis, we have measured ROS, NO, and peroxynitrite content of cancerous tissues obtained from colon and breast carcinoma cases by chemiluminescence technique. All ROS were significantly increased in cancerous colon tissues with hypochlorite making the most important contribution and suggesting the role of inflammatory cells. NO was also increased and the peroxynitrite concentration was higher in cancerous samples. For breast carcinoma cases, only O-2 .- was significantly increased. Hypochlorite was not detected excluding the contribution of inflammatory cells. NO concentrations were not significantly different, therefore, ROS might originate by change in the redox state of the tissue. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: breast cancer; colon cancer; breast cancer etiology; colon cancer etiology; free radicals; nitric oxide; NITRIC-OXIDE; FREE-RADICALS; DNA DAMAGE; CANCER; CARCINOGENESIS; CHEMILUMINESCENCE; PEROXYNITRITE; ETIOLOGY; COLITIS; ORGAN